A Dual‐Responsive Magnetoactive and Electro–Ionic Soft Actuator Derived from a Nickel‐Based Metal–Organic Framework. Issue 35 (21st July 2022) - Mahato, Manmatha; Hwang, Won‐Jun; Tabassian, Rassoul; Oh, Saewoong; Nguyen, Van Hiep; Nam, Sanghee; Kim, Ji‐Seok; Yoo, Hyunjoon; Taseer, Ashhad Kamal; Lee, Myung‐Joon; Zhang, Huapeng; Song, Tae‐Eun; et al.
Abstract: There is growing demand for multiresponsive soft actuators for the realization of natural, safe, and complex motions in robotic interactions. In particular, soft actuators simultaneously stimulated by electrical and magnetic fields are always under development owing to their simple controllability and reliability during operation. Herein, magnetically and electrically driven dual‐responsive soft actuators (MESAs) derived from novel nickel‐based metal–organic frameworks (Ni‐MOFs‐700C), are reported. Nanoscale Ni‐MOFs‐700C has excellent electrochemical and magnetic properties that allow it to be used as a multifunctional material under both magnetoactive and electro‐ionic actuations. The dual‐responsive MESA exhibits a bending displacement of 30 mm and an ultrafast rising time of 1.5 s under a very low input voltage of 1 V and also exerts a bending deflection of 12.5 mm at 50 mT under a high excitation frequency of 5 Hz. By utilizing a dual‐responsive MESA, the hovering motion of a hummingbird robot is demonstrated under magnetic and electrical stimuli. Abstract : A magnetically and electrically driven dual‐responsive soft actuator is presented by an engineering of unprecedented nickel‐based metal–organic framework (Ni‐MOF). It can nurture the complex motion for relevant robotic interaction. The magneto–electro‐ionic soft actuator obtained from the newly developed Ni‐MOF‐derived active material is successfully utilized to demonstrate hovering motion of a hummingbird robot under magnetic and electrical stimuli.